Assessment of anxiety - Mcmanus, F (2007)
This contribution reports on the assessment of anxiety and begins by discussing the different functions that assessment is used for. The nature and diagnostic features of the different types of anxiety disorders are outlined and guidance is given for differentiating between different anxiety disorders. Issues of comorbidity are discussed. Different methods used in the assessment of anxiety disorders are described. These methods include clinical and diagnostic interviews, questionnaire measures, symptom diaries and behavioural assessments. The role of assessment in devising formulations and identifying treatment targets is discussed. The iterative nature of the relationship between assessment, formulation and treatment is outlined. © 2007 Elsevier Ltd. All rights reserved.